PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SOSIOLOGI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TO STRAY (TSTS) BAGI SISWA KELAS XI IPS 2 DI SMA NEGERI 1 MIRIT - Setyaningsih, Faidah (Jurnal Analisis Pendidikan Sosial, 2024)
This research aims to find out the increasing activeness of student learning and learning outcomes through cooperative learning models two stay two stray types. This study is a class action study with the research subjects of grade XI students IPS 2 SMA Negeri 1 Mirit as many as 22 people. This research was conduced 2 cycles, each cycle consisting of 2 meeting. At each meeting consists of 4 stage namely planning, implementation, observation and reflection. Data collection techniques used include interviews and observations. Based on the results of the study, students with very high activity experienced an increase of 45?. The number of students who have high activity remains. Meanwhile, students who initially had low activity were 27? to 0?.. The average score of students increased from 52 in the initial condition to in the 64 in the first cycle. Then it increased again to 82 in the second cycle. Thus, it can be concluded that through cooperative learning models two stay two stray tipes can increase the active learning and learning outcomes of grade XI students of SMA Negeri 1 Mirit.